GESTÃO DE SEGURANÇA DO TRABALHO NAS PARADAS DE MANUTENÇÃO EM REFINARIA DE PETRÓLEO - Veiga, Daniel Faria da (2004)
The aspects of Safety Management in a maintenance turnaround in a oil refinery are presented, with a focus on one of its most important tool: The Turnaround Safety Plan.The aplication of specific itens of this Plan to the non conformities detected in the development of the turnaround are described with commentaries, including the right steps to correctly associate the item in the Plan with the specific occurency.The main purpose for this kind of application and its results is the continuous improvement in the prevention of accidents and hazardous conditions in a critical period of work like scheduled maintenance turnaround.